As a result of the legal issuance of the Financial Services Authority Regulation on the Obligation to Fulfill the Minimum Core Capital for the Existence of People's Economic Banks (Study on PT. People's Economic Bank Straightforward Dana Mandiri Padang) - Arisman Susanto; Susi Delmiati; Laurensius Arliman (Master of Law Program, Ekasakti University, 2025)
Article 13 of the Financial Services Authority Regulation (POJK) Number 5/POJK/03/2015 concerning Minimum Core Capital Provisions for People's Credit Banks has required all People's Credit Banks to fulfill the minimum core capital of Rp. 6 billion until the deadline ending December 31, 2024. Based on the above provisions, Bank Perkreditan Rakyat which does not have a core capital of Rp. 6 billion must find funds, including by selling its personal assets, looking for new investors and also for shareholders to sell their Bank Perkreditan Rakyat to other parties. The approach of this research is normative juridical supported by empirical juridical juridical The data used in this study are secondary data and primary data in the form of interviews. Based on the results of the research, the discussion and analysis were concluded. First, the legal consequences of the issuance of financial services authority regulations regarding the obligation to fulfill the minimum core capital for the existence of the People's Economic Bank are subject to administrative sanctions in the form of: 1) it is stated that the health level of BPR has decreased; 2) it is forbidden to open an office network; 3) it is prohibited to carry out Foreign Exchange Business Activities and electronic banking device services; 4) subject to restrictions on the area of disbursement of funds to one district that is the same as the location of the BPR office; 5) subject to remuneration restrictions or other forms equivalent to it to members of the Board of Commissioners and/or the Board of Directors of BPR, or in return to related parties, 6) revocation of BPR's operational license. Second, the obstacles faced in the implementation of the Financial Services Authority Regulation on the obligation to fulfill the minimum core capital by the People's Economic Bank are divided into two, namely: legal and non-legal constraints. Legal obstacles are 1) limited BPR business activities, 2) merger efforts (consolidation) can eliminate the historical traces of BPR Lugas Dana Mandiri, 3) takeover efforts have the potential to cause the relocation of BPR business locations, and non-legal obstacles, namely; 1) the financial ability of BPR shareholders, 2) the existence of sectoral egos in BPR merger efforts.